Qiwamah's Reconception of Muhammad Shahrur's Thoughts and Their Implications for the Feminist Movement in the World - Nelli, Jumni; Harmanto, Adi; Hardani, Sofia; Syu'aib, Kholil; Megawati, Devi (Institut Agama Islam Negeri Curup, 2024)
This research aims to reconceptualize Muhammad Syahrur's views on the meaning of qiwamah. Muhammad Syahrur stated that the person most worthy of being qiwamah in the household is a woman. This view is different from the Jumhur Ulama which states that the leader in the household is a man. Does Shahrur's thoughts support the world feminist movement? This library research was carried out by examining books related to the research problem. Primary data sources are the books Al Kitab Wa Al Qur'an and Nahwa Ushul Jadidah Li Al-Fiqh Al-Islami by Muhammad Syahrur. Secondary data sources were obtained from other fiqh books and journals related to the problems in this paper. Descriptive analysis uses the content analysis method. The results of the research found that Syahrur is of the view that qiwamah can be played by husband or wife, as long as it has stability in the economic sector and the characteristics of qiwamah, namely shalihat, qanitat and hafizat; because these qiwamah qualities were firmly instilled by Allah, as qualities possessed by women, the ones most worthy of being appointed as qiwamah are women; Even though Syahrur only relies on linguistic analysis, and ignores the study of the context of the Asbab al Nuzul verse, resulting in inconsistencies and meanings that seem forced, Shahrur's thoughts seem to have given encouragement to the feminist movement in the world. Muhammad Shahrur's breakthrough feminist thought influenced the thinking of Muslim women in the world. This can be seen from the change in their mindset, who no longer want to simply follow or be controlled by men. Contemporary Islamic thinkers agree to provide leadership to men and women with conditions, but they do not say that women are the main leaders.